PENGARUH PERIKLANAN DAN BRAND AMBASSADOR TERHADAP MINAT BELI KONSUMEN E-COMMERCE - Annisa Rahayu Agustine (PT Naureen Digital Education, 2023)
This study aims to analyze the effect of advertising and brand ambassadors on the buying interest of Tokopedia e-commerce consumers. The method of determining the sample used is purposive sampling. The sample in this study were 100 Tokopedia users in Sukabumi City. The analytical method used in this research is multiple linear regression analysis. The results of this study indicate that: (1) Advertising has a positive effect on the buying interest of Tokopedia consumers. (2) Brand Ambassador has a positive effect on Tokopedia consumers' buying interest. (4) Advertising and Brand Ambassadors have a positive effect on consumer buying interest. The magnitude of the influence of Advertising and Brand Ambassadors on Consumer Buying Interest is evidenced by the adjusted R square value of 0.632 indicating that the ability of the independent variable in explaining the variation of the dependent variable is 63,2% and the remaining 36,8% is explained by other variables outside this research model.